Factors Affecting Tuberculosis Preventive Behaviors among People with Tuberculosis Contact in Bang Krathum District, Phitsanulok Province - Thomtong, Thitima; Sudnongbua, Supaporn (Journal of Phrapokklao Nursing College, Chanthaburi, 2023)
This predictive correlational research aimed to study factors affecting tuberculosis preventive behaviors among people with tuberculosis contact. The samples were 170 people with tuberculosis contact in Bang Krathum District, Phitsanulok Province. The research instruments included the personal factors interview form, the knowledge about tuberculosis interview form with a reliability of .74, the personal perceived factors interview form with a reliability of .90, the inducers of tuberculosis preventive behaviors interview form with a reliability of .96, and the tuberculosis preventive behaviors interview form with a reliability of .98. Data were collected from June to September 2019. Statistics used for data analysis included frequency, percentage, mean, standard deviation, and stepwise multiple regression analysis. The research results revealed that the mean score of tuberculosis preventive behaviors among people with tuberculosis contact was at a moderate level (M = 2.80, SD = .31). Gender (female) and inducers of tuberculosis preventive behaviors could statistically significantly jointly predict tuberculosis preventive behaviors among people with tuberculosis contact at 27.90% (adj. R2 = .279, p < .001). The most predicting factor was inducers of tuberculosis preventive behaviors (Beta = .529, p < .001). This research suggests that health care workers should perform home visit for people with tuberculosis contact continuously as well as provide tuberculosis advice and protective equipment. This will help people with tuberculosis contact gain motivation and enhance their tuberculosis preventive behaviors.